Distribution, natural history, and conservation of the Patagonian Weasel Lyncodon patagonicus - Prevosti, Francisco Juan (2009)
The Patagonian Weasel Lyncodon patagonicus is a small mustelid that lives in the Southern Cone of South America (Argentina and Chile). The species is known from relatively few direct observations and collected specimens. In this paper we review available data about L. patagonicus to assess its conservation status. Information about its natural history is largely anecdotal, and suggests that it feeds on fossorial rodents. Known record localities are based on specimens observed or collected during the nineteenth and twentieth centuries. Its distribution encompasses herbaceous and shrub steppes and xerophytic woodlands, and presumably includes protected areas. However, the presence of L. patagonicus in these areas must be reconfirmed, because most records of occurrence are more than 10 years old. The perceived scarcity of this species in the wild could be real, but its relatively widespread distribution might protect it from the effects of environmental alteration and other human impacts. We conclude that field studies are urgently needed to confirm the current distribution and ecological requirements of the Patagonian Weasel.